RELEVANSI KONSEP PENDIDIKAN KARAKTER MENURUT IMAM IBNU JAMA’AH DALAM KITAB TAZKIRAH AS-SAMI’ WA AL-MUTAKALLIM FI ADAB AL-՝ALIM WA AL-MUTA՝ALLIM DENGAN PENDIDIKAN KARAKTER DI INDONESIA - Al Busthomi, Muhammad Yazid; Rifqi Junaidi, Mohammad (University of Islam Malang, 2024)
Education in Indonesia currently emphasizes the importance of the character of the future generations. The government implements character education as a primary strategy to address the decline in character. The book